1979
DOI: 10.1159/000122948
|View full text |Cite
|
Sign up to set email alerts
|

Compared Localizations of Prolactin-Like and Adrenocorticotropin Immunoreactivities within the Brain of the Rat

Abstract: By an immunoperoxidase (PAP) technique, ACTH- and prolactin-like substances were detected in neurons of several hypothalamic nuclei in young and adult rats. Neurons in the arcuate and ventromedial nuclei were simultaneously both ACTH-like and PRL-like positive. Labelled fibres were followed to their fields of projections. Intensity of labelling was not influenced by experimental procedures known to change PRL and ACTH content of the pituitary. Colchicine enhanced labelling of perikarya while lowering that of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
18
0

Year Published

1980
1980
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(24 citation statements)
references
References 24 publications
(36 reference statements)
6
18
0
Order By: Relevance
“…Immunoreactive LH was also found in scattered cells of the pars tuberalis, in agreement with findings from other stud ies [7,8], The distribution of radioimmunoassayble LH in the rat brain is rather similar to that also reported for ACTH [13,16,19] and TSH [15]. It is of interest to note also that the distribution of stained neural elements is simular to that reported for ACTH [26] and prolactin [25] although much less intense than that obtained by us for ACTH [10]. This suggests that several adenohypophysial principles may coexist in separate or identical arcuate perikarya, and that their fiber processes project to hypothalamic and extrahypothalamic sites.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Immunoreactive LH was also found in scattered cells of the pars tuberalis, in agreement with findings from other stud ies [7,8], The distribution of radioimmunoassayble LH in the rat brain is rather similar to that also reported for ACTH [13,16,19] and TSH [15]. It is of interest to note also that the distribution of stained neural elements is simular to that reported for ACTH [26] and prolactin [25] although much less intense than that obtained by us for ACTH [10]. This suggests that several adenohypophysial principles may coexist in separate or identical arcuate perikarya, and that their fiber processes project to hypothalamic and extrahypothalamic sites.…”
Section: Discussionsupporting
confidence: 91%
“…Obviously, this suggestion requires further careful studies of antibody specificity and possible antigen ic cross reactivity. However, supporting evidence for this suggestion comes from the localization of prolactin and ACTH within the same arcuate perikarya [25].…”
Section: Discussionmentioning
confidence: 95%
“…The selective localization of positive cells in the peripheral part of the paraventricular nucleus and in the dorsal part of the supraoptic nucleus is similar to the localization of oxytocin neurones (24); in view of the number of positive magnocellular cells and of positive posthypophyseal fibers, it can be suggested that this positive material is located mainly in oxytocin neurons. Such a localization of two unrelated peptides in the same neuron has been described for corticotropin and prolactin in the hypothalamic arcuate, ventromedial, and premamillary nuclei (25).…”
Section: Methodssupporting
confidence: 60%
“…We have previously shown that T implants in the POA-SCN can specifically inhibit DA turnover locally [33]. There are some neurons in the rostral POA regions which contain 'prolactin-like' material [12,38,39] and electrophysiological studies have also identified prolactin-responsive neu rons in the POA [8]. The results of the present studies further reveal the existence of a complex interaction between the androgen-concentrating neurons [35,36] and prolactin-re sponsive cells in the POA-SCN [8] to modulate the activity of DA neurons locally.…”
Section: Discussionmentioning
confidence: 99%